Effect of biocorrective supplements on functional and technological properties of complex food systems - T. V. Alexeeva; E. S. Popov; L. A. Albycheva; Yu. O. Kalgina (Новые технологии, 2021)
The article presents the results of studies on the effect of a bio-correcting food supplement on functional and technological properties of model liver-based pate systems. The supplement included components that are domestic resource-saving sources with predictable biopotential and consumer properties. The food-fortifying supplement was added to the model pate systems in the amount of 10–30%. The aim of the research is to study the effect of bio-correcting supplement on functional and technological properties of liver pate products. Technology of preparing model minced meat systems, along with traditional operations, included the stage of introducing a bio-correcting supplement into the cutter. It has been found that dry supplement components must be hydrated when used in the composition of pate recipes. The process of hydration of the enriching supplement was carried out with drinking water in the ratio of 1:2, and was stirred to a homogeneous state, then kept at the temperature of 19 ± 5°C for 10–15 minutes. That corresponded to the state of saturation of the system biopolymers with moisture and achievement of a pasty consistency, similar to that of pate masses. In the course of the research it was found that the model compositions had higher indicators of functional and technological properties compared with the control ones. The enriching additive in the composition of liver pate increased up to 30% compared with the samples prepared according to the traditional recipe: the moisture-binding capacity by 11–20%, the water-holding capacity by 20–25%, and the emulsifying capacity by 9–14%. The results obtained indicate the possibility of a targeted influence of the additive components on the functional and technological properties of liver pate. When a bio-correcting additive is included in liver pates, the pates get enriched with high-grade protein, vitamins, minerals and essential substances; organoleptic properties of finished products improve; calorie content of products reduces; functional, technological, structural and mechanical properties improve; the risk of broth-fat edema and moisture release from food products reduces; thermal losses decrease and the yield of finished products increases; a new product line of pates with high biopotential and consumer properties is obtained.